Quantitative Longitudinal Imaging of Vascular Inflammation and Treatment by Ezetimibe in apoE Mice by FMT Using New Optical Imaging Biomarkers of Cathepsin Activity and αvβ3 Integrin. (17th October 2012) - Lin, Shu-An; Patel, Manishkumar; Suresch, Donna; Connolly, Brett; Bao, Bagna; Groves, Kevin; Rajopadhye, Milind; Peterson, Jeffrey D.; Klimas, Michael; Sur, Cyrille; Bednar, Bohumil
Abstract : Inflammation as a core pathological event of atherosclerotic lesions is associated with the secretion of cathepsin proteases and the expression ofα v β 3 integrin. We employed fluorescence molecular tomographic (FMT) noninvasive imaging of these molecular activities using cathepsin sensing (ProSense, CatB FAST) andα v β 3 integrin (IntegriSense) near-infrared fluorescence (NIRF) agents. A statistically significant increase in the ProSense and IntegriSense signal was observed within the chest region of apoE −/− mice (P < 0.05 ) versus C57BL/6 mice starting 25 and 22 weeks on high cholesterol diet, respectively. In a treatment study using ezetimibe (7 mg/kg), there was a statistically significant reduction in the ProSense and CatB FAST chest signal of treated (P < 0.05 ) versus untreated apoE −/− mice at 31 and 21 weeks on high cholesterol diet, respectively. The signal of ProSense and CatB FAST correlated with macrophage counts and was found associated with inflammatory cells by fluorescence microscopy and flow cytometry of cells dissociated from aortas. This report demonstrates that cathepsin andα v β 3 integrin NIRF agents can be used as molecular imaging biomarkers for longitudinal detection of atherosclerosis, and cathepsin agents can monitor anti-inflammatory effects of ezetimibe with applications in preclinical testing of therapeutics and potentially for early diagnosis of atherosclerosis in patients.